2016
DOI: 10.1073/pnas.1611631113
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobicity enhancement through substrate flexibility

Abstract: Inspired by manifestations in nature, microengineering and nanoengineering of synthetic materials to achieve superhydrophobicity has been the focus of much work. Generally, hydrophobicity is enhanced through the combined effects of surface texturing and chemistry; being durable, rigid materials are the norm. However, many natural and technical surfaces are flexible, and the resulting effect on hydrophobicity has been largely ignored. Here, we show that the rational tuning of flexibility can work synergisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(156 citation statements)
references
References 48 publications
15
141
0
Order By: Relevance
“…Note however that most studies have focused on rigid surfaces and neglected the flexibility of the substrate, which is inherent to most naturally occurring repellent surfaces such as leaves, textiles or butterfly wings. Notable is the recent study of [63], where the effect of elasticity on hydrophobicity was investigated experimentally.…”
Section: B Extensions To Fluid-structure Interaction In Multiphase Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Note however that most studies have focused on rigid surfaces and neglected the flexibility of the substrate, which is inherent to most naturally occurring repellent surfaces such as leaves, textiles or butterfly wings. Notable is the recent study of [63], where the effect of elasticity on hydrophobicity was investigated experimentally.…”
Section: B Extensions To Fluid-structure Interaction In Multiphase Flowmentioning
confidence: 99%
“…In this section, we aim to go beyond classical benchmark cases and explore the capabilities of the KBC-FSI solver in the context of multiphase flows by considering droplet impact on flexible superhydrophobic surfaces, similar to [63]. From the numerical point of view, simulations of such a kind are challenging.…”
Section: B Extensions To Fluid-structure Interaction In Multiphase Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact force of the droplet, which scales as F ∼ ρU 0 2 πD 0 2 , 23 excites the flexible surface to vibrate at its first-mode natural frequency, f s = (1/2π) √ k s /m s . [24][25][26] Here, m s is the effective mass and k s is the flexural rigidity. During spreading, the initial kinetic energy of the droplet converts to the elastic energy of the flexible surface and the surface energy of the droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, natural superhydrophobic materials are usually of good flexibility, whose effect on the wetting performance has long been ignored. It is only recently found that substrate flexibility enhances superhydrophobic performance along with surface microstructures synergistically . For instance, extended water repellency can be attributed to substrate flexibility, and other droplet effects such as impalement resistance and droplet‐substrate contact time also benefit from flexible feature.…”
Section: Introductionmentioning
confidence: 99%